Pertumbuhan Cangkang Kerang Mutiara Pteria penguin yang Diimplantasi yang Dibudidayakan dengan Metode Gantung di Perairan Palabusa Selat Buton - Mushaffa, Waode; Hamzah, Muhaimin; Nur, Indriyani (JSIPi (Jurnal Sains dan Inovasi Perikanan) (Journal of Fishery Science and Innovation), 2018)
The producing half-pearls (Mabe) at the Palabusa waters of Buton Strait Southeast Sulawesi still uses simple technology, namely applying implantation with only a single nuclei, which has an impact on the large number of seeds and used space. Therefore, in order to increase the production of mabe pearls, one of effort is by planting two nucleus in a single mabe pearl shell. The test animals used were P. penguin as many as 90 oysters, with an average length of 12 cm shells, 8 cm shell height and 100-120 g individual weights. The nucleus used was made from plastic (half round) with diameter of 10 cm and height of 0.8 cm. This research was conducted for four months. The study was designed using a completely randomized design with 3 treatments and 3 replications. The treatment applied was A (a nucleus was inserted into the left shell), B (2 nuclei were inserted into the left shell), and C (a nucleus was inserted into each on the left and right shells). The results showed that all treatments did not have a significant effect on the growth of shells. Hence, the addition of two nuclei in a single pearl oyster can be used to increase cultivation production.Â Keywords : Pteria penguin, implantation, nucleus, growth